Method for detecting fragment carbon content in lithium iron phosphate positive electrode material

By dispersing the lithium iron phosphate material in the solvent, the density difference is used for fragmented carbon to solve the problem that the existing detection method cannot objectively judge the carbon content of fragments, and achieves fast and accurate test results.

CN119375083APending Publication Date: 2025-01-28SHANGHAI RUIPU ENERGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411546363.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28

Smart Images

  • Figure BDA0005115053220000111
    Figure BDA0005115053220000111
  • Figure BDA0005115053220000121
    Figure BDA0005115053220000121
Patent Text Reader

Abstract

The invention relates to the technical field of lithium iron phosphate material detection, in particular to a method for detecting the content of fragment carbon in a lithium iron phosphate positive electrode material, which comprises the following steps: dispersing the lithium iron phosphate positive electrode material in a solvent to obtain a dispersion liquid, and standing the dispersion liquid; the dispersion liquid obtained after standing treatment is taken from the upper layer according to 30-60% of the total volume of the dispersion liquid and dried, the mass of the dried material is M1, and the carbon content is C1; the remaining dispersion liquid is dried, the mass of the dried material is M2, and the carbon content is C2; and calculating and obtaining the fragment carbon content in the lithium iron phosphate positive electrode material according to a formula: (C1-C2) * M1 / (M1 + M2). According to the method, multiple factors in the detection process are explored, and the formula is designed, so that the content of the fragment carbon in the lithium iron phosphate material can be rapidly detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium iron phosphate material detection, and in particular to a method for detecting the carbon content of fragments in a lithium iron phosphate positive electrode material. Background Art

[0002] Compared with high energy density ternary lithium batteries, lithium iron phosphate batteries have attracted much attention due to their advantages such as high safety and low cost, and have been widely used in the new energy industry. However, due to the defects of small lithium ion diffusion coefficient and low electronic conductivity, lithium iron phosphate materials have poor low temperature performance and high rate charge and discharge performance and low energy density, which makes it difficult to meet people's demand for battery life.

[0003] As one of the most important technologies for modifying lithium iron phosphate materials, surface carbon coating can enhance the electronic conductivity between particles on the one hand, and block the lithium iron phosphate material and the electrolyte on the other hand, thereby protecting the surface of the material and reducing the occurrence of side reactions. However, as an inactive substance, the introduction of the graphitized carbon layer will lead to a decrease in the specific capacity of the lithium iron phosphate material. At the same time, in the synthesis process of lithium iron phosphate materials, composite carbon sources are often used to achieve the coating effect. Under ideal conditions, after the carbon source is melted, it adheres to the surface of the iron phosphate precursor and lithium carbonate due to surface tension, and acts as a reducing agent and a coating agent at the same time. However, the carbonization of the carbon source does not depend on the precursor and the lithium source. Commonly used glucose and polyethylene glycol (PEG) can spontaneously form carbon under an inert gas atmosphere. The carbon species formed at high temperature may be mixed in the powder material in a completely free manner (free carbon), or may form independent species (non-coated carbon) in a non-coated form on the surface of the material. These free carbon and non-coated carbon together constitute fragmented carbon. Fragmentary carbon can play a partial conductive role, but its supporting effect during particle accumulation will seriously affect the compaction of the material, resulting in a decrease in the compaction density of the powder. In addition, fragmentary carbon also has a strong lyophobicity and is prone to aggregation in polar solvents, resulting in the powder particle material being unable to be evenly dispersed. Therefore, it is particularly important to achieve effective carbon coating while minimizing the amount of carbonaceous materials used, especially to reduce the amount of fragmentary carbon generated during coating. The current means of observing the coating effect of materials are mainly scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The detection method is relatively limited, and the observation of the coating effect of materials through SEM and TEM is a subjective evaluation, that is, the existing detection method cannot objectively judge the content of fragmentary carbon. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the existing method for detecting the carbon content of fragments in lithium iron phosphate positive electrode materials cannot objectively judge its content, thereby providing a method for detecting the carbon content of fragments in lithium iron phosphate positive electrode materials to solve the above problem.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A method for detecting the carbon content of fragments in a lithium iron phosphate positive electrode material, comprising: dispersing the lithium iron phosphate positive electrode material in a solvent to obtain a dispersion, and subjecting the dispersion to a static treatment; wherein, based on the mass of the lithium iron phosphate positive electrode material being 1 g, the amount of the solvent used is not less than 30 mL; the dispersion time is 10-60 min, and the static treatment time is not less than 40 min; the density of the solvent is lower than that of the lithium iron phosphate material;

[0007] 30-60% of the total volume of the dispersion is removed from the upper layer and dried. The mass of the dried material is M1 and the carbon content is C1.

[0008] The remaining dispersion is dried, and the mass of the material after drying is M2, and the carbon content is C2;

[0009] The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated using the formula: (C1-C2)×M1 / (M1+M2).

[0010] Preferably, based on the mass of the lithium iron phosphate positive electrode material being 1 g, the amount of the solvent used is 30-100 mL.

[0011] Preferably, the solvent is at least one of water, ethanol, methanol, benzene and N-methylpyrrolidone.

[0012] Preferably, the dispersion is carried out by ultrasonic treatment.

[0013] Preferably, the static treatment time is 40 minutes to 10 hours.

[0014] Preferably, the method of removing the dispersion liquid includes at least one of quantitative pipetting and centrifugation.

[0015] Preferably, the dispersion is pipetted by quantitative aspiration.

[0016] Preferably, the drying process is performed by oven drying.

[0017] Preferably, the carbon content is detected by an instrument.

[0018] Preferably, the instrument is a high-frequency infrared carbon-sulfur analyzer.

[0019] The technical solution of the present invention has the following advantages:

[0020] 1. A method for detecting the carbon content of fragments in a lithium iron phosphate positive electrode material, comprising: dispersing the lithium iron phosphate positive electrode material in a solvent to obtain a dispersion, and standing the dispersion; wherein, based on the mass of the lithium iron phosphate positive electrode material being 1g, the amount of the solvent used is not less than 30mL; the dispersion time is 10-60min, and the standing time is not less than 40min; the density of the solvent is lower than that of the lithium iron phosphate material; 30-60% of the total volume of the dispersion is removed from the upper layer after the standing treatment and dried, the mass of the material after drying is M1, and the carbon content is C1; the remaining dispersion is dried, the mass of the material after drying is M2, and the carbon content is C2; the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated by the formula: (C1-C2)×M1 / (M1+M2). Among them, the amount of solvent is limited to not less than 30mL so that the formed dispersion has sufficient volume to disperse low-density species; the dispersion time is limited to 10-60min, because a dispersion time of less than 10min is insufficient to disperse the fragment carbon species, and exceeding 60min may cause damage to the material, thereby increasing the detected fragment carbon content; the standing time is not less than 40min, because a short standing time will result in the components without fragment carbon not being deposited to the bottom of the container; the upper dispersion transfer ratio is limited to 30%-60% of the total volume of the dispersion, because if the ratio is too low, it is easy to encounter the problem that the components in the upper dispersion transferred are too few and below the limit that the equipment can measure, and if the ratio is too high, the components without fragment carbon after partial sedimentation may be transferred, affecting the accuracy of the results.

[0021] The present invention can quickly detect the content of fragment carbon in lithium iron phosphate materials by exploring and verifying multiple factors in the detection process and designing formulas. That is, it can simply and quickly objectively evaluate the carbon coating effects of different lithium iron phosphate materials, thereby helping to judge the material characteristics, quality and process risks during the development and use of lithium iron phosphate materials. The principle of the present invention is to use solvents to distinguish components with different densities in the material to achieve the purpose of detecting fragment carbon. Among them, the true density of lithium iron phosphate material is about 3.6g / cc, which is higher than water and many common organic solvents; the density of free fragment carbon and fragment carbon attached to the surface of the material is close to that of graphene. Although it does not have a definite true density as a two-dimensional material, its actual density after forming a folded structure will be much lower than the true density of graphite 2.3g / cc. Free carbon and non-coated carbon have poor binding effects with the main material and are easily separated from the main material particles during the dispersion process. Free carbon and non-coated carbon are light in weight and small in particles, so they will be enriched in the upper dispersion. After the upper dispersion is dried, it will show a low-density component, and after the lower dispersion is dried, it will show a high-density component. Based on this technical concept, the present invention first disperses all the different density components of the material evenly, and then uses the density difference and sedimentation velocity difference of different components to enrich the component containing fragment carbon in the upper dispersion, so as to test the fragment carbon content.

[0022] 2. In the method for detecting the carbon content of fragments in the lithium iron phosphate positive electrode material of the present invention, the amount of solvent used is preferably 30-100 mL, based on the mass of the lithium iron phosphate positive electrode material being 1 g. That is, the volume of the solvent should not be too high. When it exceeds 100 mL, the detection effect will not be improved, but the drying time needs to be extended. Therefore, for energy-saving considerations, the amount of solvent used is limited to 30-100 mL.

[0023] 3. In the method for detecting the carbon content of fragments in the lithium iron phosphate positive electrode material of the present invention, the standing time is further limited to 40min-10h. This is because if the standing time is too long, on the one hand, it will not improve the test accuracy, and on the other hand, it may cause the components in the upper dispersion liquid to be too few and below the limit that the equipment can measure. DETAILED DESCRIPTION

[0024] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0025] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0026] Example 1

[0027] This embodiment provides a method for detecting the carbon content of fragments in a lithium iron phosphate positive electrode material. The test results are shown in Table 1. The specific steps are as follows:

[0028] 1) Take 2g of lithium iron phosphate material (sample 1) and place it in a conical flask, add 100mL of ethanol, use 100kHz ultrasound for 10min and then let it stand for 4h;

[0029] 2) Use a pipette to take 30 mL of the upper dispersion in a conical flask and place it in a small beaker, place the small beaker in a blast drying oven, bake at 100°C for 10 h, collect the solid powder after drying and use a high-frequency infrared carbon-sulfur analyzer to test the carbon content. The mass of the solid powder is M1 (0.1256 g) and the carbon content is C1 (3.765%); wherein, the specific steps of using the high-frequency infrared carbon-sulfur analyzer to test the carbon content are: weigh 0.2 g of tin co-solvent into a crucible, then weigh 0.1 g of the solid powder sample and add 1.4 g of tungsten particles, then place the crucible into the crucible support of the high-frequency infrared carbon-sulfur analyzer, click "Lift" to raise it into the reactor, click to start analysis, and record the data after the test is completed;

[0030] 3) The conical flask containing the remaining dispersion was placed in a forced air drying oven and baked at 100°C for 10 h. After drying, the solid powder was collected and the carbon content was tested using a high-frequency infrared carbon-sulfur analyzer (the test method was the same as above). The mass of the solid powder was M2 (1.8758 g) and the carbon content was C2 (1.203%).

[0031] 4) The carbon content of the fragments in the lithium iron phosphate positive electrode material was calculated to be 0.161% by the formula: (C1-C2)×M1 / (M1+M2).

[0032] Example 2

[0033] The difference between this embodiment and embodiment 1 is that the amount of ethanol added in step 1) is 150 mL, 45 mL of the upper dispersion liquid is taken in step 2), and the rest is the same as in embodiment 1, and the sample is obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1301 g, C1 is 3.696%, M2 is 1.872 g, and C2 is 1.197%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.162% according to the formula (C1-C2)×M1 / (M1+M2).

[0034] Example 3

[0035] The difference between this embodiment and embodiment 1 is that the ultrasonic time in step 1) is 60 minutes, and the rest is the same as embodiment 1, and the sample is obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1282g, C1 is 3.769%, M2 is 1.8723g, C2 is 1.199%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated according to the formula (C1-C2)×M1 / (M1+M2) to be 0.165%.

[0036] Example 4

[0037] The difference between this embodiment and embodiment 1 is that the standing time after ultrasound in step 1) is 40 minutes, and the rest is the same as in embodiment 1, and the samples are obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1475g, C1 is 3.488%, M2 is 1.8535g, C2 is 1.207%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated according to the formula (C1-C2)×M1 / (M1+M2) to be 0.168%.

[0038] Example 5

[0039] The difference between this embodiment and embodiment 1 is that the standing time after ultrasound in step 1) is 2 hours, and the rest is the same as in embodiment 1, and the samples are obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1374g, C1 is 3.597%, M2 is 1.8633g, C2 is 1.199%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.165% according to the formula (C1-C2)×M1 / (M1+M2).

[0040] Example 6

[0041] The difference between this embodiment and embodiment 1 is that the standing time after ultrasound in step 1) is 10 hours, and the rest is the same as in embodiment 1, and the samples are obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1219 g, C1 is 3.829%, M2 is 1.879 g, and C2 is 1.195%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.160% according to the formula (C1-C2)×M1 / (M1+M2).

[0042] Example 7

[0043] The difference between this embodiment and embodiment 1 is that the solvent used in step 1) is deionized water, and the rest is the same as embodiment 1. The samples are obtained for carbon content testing, and the test results are shown in Table 1. In this embodiment, M1 is 0.1472g, C1 is 3.49%, M2 is 1.8545g, C2 is 1.20%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated according to the formula (C1-C2)×M1 / (M1+M2) to be 0.168%.

[0044] Example 8

[0045] The difference between this embodiment and embodiment 1 is that in step 1), lithium iron phosphate (sample No. 2) is taken for testing, and the rest is the same as in embodiment 1, and the sample is obtained for carbon content testing, and the test results are shown in Table 1. In this embodiment, M1 is 0.2403g, C1 is 3.552%, M2 is 1.7617g, C2 is 1.18%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.285% according to the formula (C1-C2)×M1 / (M1+M2).

[0046] Example 9

[0047] The difference between this embodiment and embodiment 1 is that in step 1), lithium iron phosphate (sample No. 3) is taken for testing, and the rest is the same as in embodiment 1, and the sample is obtained for carbon content testing, and the test results are shown in Table 1. In this embodiment, M1 is 0.1002g, C1 is 3.729%, M2 is 1.8996g, C2 is 1.201%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.127% according to the formula (C1-C2)×M1 / (M1+M2).

[0048] Example 10

[0049] The difference between this embodiment and embodiment 1 is that in step 1), lithium iron phosphate (sample No. 4) is taken for testing, and the rest is the same as in embodiment 1, and the sample is obtained for carbon content testing, and the test results are shown in Table 1. In this embodiment, M1 is 0.2201g, C1 is 4.112%, M2 is 1.781g, and C2 is 1.322%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.307% according to the formula (C1-C2)×M1 / (M1+M2).

[0050] Embodiment 11

[0051] The difference between this embodiment and embodiment 8 is that the solvent used in step 1) is deionized water, and the rest is the same as embodiment 8, and the samples are obtained for carbon content testing, and the test results are shown in Table 1. In this embodiment, M1 is 0.2788g, C1 is 3.307%, M2 is 1.7236g, C2 is 1.167%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated according to the formula (C1-C2)×M1 / (M1+M2) to be 0.298%.

[0052] Example 12

[0053] The difference between this embodiment and embodiment 1 is that, in step 2), after standing, 50 mL of the upper solution is taken for drying, and the rest is the same as in embodiment 1, and the sample is obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1301 g, C1 is 3.662%, M2 is 1.8708 g, C2 is 1.189%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated according to the formula (C1-C2)×M1 / (M1+M2) to be 0.161%.

[0054] Embodiment 13

[0055] The difference between this embodiment and embodiment 1 is that the amount of ethanol added in step 1) is 60 mL, 30 mL of the upper dispersion liquid is taken in step 2), and the rest is the same as in embodiment 1, and the sample is obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1644 g, C1 is 3.185%, M2 is 1.8373 g, C2 is 1.190%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.164% according to the formula (C1-C2)×M1 / (M1+M2).

[0056] Embodiment 14

[0057] The difference between this embodiment and embodiment 1 is that the amount of ethanol added in step 1) is 200 mL, 120 mL of the upper dispersion liquid is taken in step 2), and the rest is the same as in embodiment 1, and the sample is obtained for carbon content test, and the test results are shown in Table 1. In this embodiment, M1 is 0.1829 g, C1 is 2.986%, M2 is 1.8179 g, C2 is 1.20%, and the carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.163% according to the formula (C1-C2)×M1 / (M1+M2).

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that 40 mL of ethanol is added in step 1), and the rest is the same as Example 1. The samples are tested for carbon content, and the test results are shown in Table 1. In this comparative example, M1 is 0.1521 g, C1 is 3.027%, M2 is 1.8498 g, and C2 is 1.231%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.136% according to the formula (C1-C2)×M1 / (M1+M2).

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that the ultrasonic time in step 1) is 5 minutes, and the rest is the same as Example 1. The samples were tested for carbon content, and the test results are shown in Table 1. In this comparative example, M1 is 0.1449 g, C1 is 3.155%, M2 is 1.8555 g, and C2 is 1.229%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.140% according to the formula (C1-C2)×M1 / (M1+M2).

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that the ultrasonic time in step 1) is 2 hours, and the rest is the same as Example 1. The samples were tested for carbon content, and the test results are shown in Table 1. In this comparative example, M1 is 0.1273 g, C1 is 3.998%, M2 is 1.8745 g, and C2 is 1.186%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.179% according to the formula (C1-C2)×M1 / (M1+M2).

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that the standing time after ultrasound in step 1) is 30 minutes, and the rest is the same as Example 1. The samples were tested for carbon content, and the test results are shown in Table 1. In this comparative example, M1 is 0.1399 g, C1 is 3.341%, M2 is 1.8597 g, and C2 is 1.211%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.149% according to the formula (C1-C2)×M1 / (M1+M2).

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that in step 2), 80 mL of the upper solution is taken out for drying after standing, and the rest is the same as Example 1, and the obtained sample is tested for carbon content, and the test results are shown in Table 1. In this comparative example, M1 is 0.1565 g, C1 is 3.001%, M2 is 1.845 g, and C2 is 1.233%. The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated to be 0.138% according to the formula (C1-C2)×M1 / (M1+M2).

[0068] Table 1

[0069]

[0070]

[0071] According to the experimental results of the embodiments and comparative examples, the present invention can obtain relatively stable test results by regulating multiple variables and using formula conversion, and can clearly distinguish different samples. Using the detection method provided by the present invention, the uniformity of carbon coating of lithium iron phosphate materials can be simply and quickly determined.

[0072] Specifically, according to the comparison between Example 1 and Example 2, Example 13, and Example 14, the amount of solvent within the range has little effect on the results.

[0073] Comparing Example 1 with Example 3, the ultrasound time within the range has little effect on the results.

[0074] Comparing Example 1 with Examples 4-6, the standing time has a certain influence on the results, but the difference is not large and gradually converges to a stable value.

[0075] Compared with Example 1 and Example 7, the change of solvent will have a certain impact on the results. The effect of increasing the solvent density is similar to shortening the standing time, but the test results are not much different and are relatively stable.

[0076] Comparing Example 1 with Examples 8-10, it can be seen that the detection method of the present invention has obvious resolution for different materials.

[0077] Comparing Example 8 with Example 11, it can be seen that the influence of changing the solvent on the results has a similar trend, and the stability of the method can be verified.

[0078] Comparing Example 1 with Example 12, it can be seen that the amount of the upper dispersion liquid taken has a certain influence on the result, but the influence within the range is not significant.

[0079] Comparison between Example 1 and Comparative Example 1 shows that too little solvent significantly affects the resolution of the method. In this case, it is difficult to separate the carbon species containing fragments from the carbon species not containing fragments.

[0080] By comparing Example 1 with Comparative Example 2, it can be seen that too short an ultrasonic time will also affect the resolution of the method, resulting in a lower carbon content in the fragments in the result.

[0081] By comparing Example 1 with Comparative Example 3, it can be seen that too long an ultrasonic time will lead to an increase in the proportion of carbon in the fragments, resulting in a low carbon content in the fragments in the results.

[0082] By comparing Example 1 with Comparative Example 4, it can be seen that too short a standing time will affect the resolution of the method, resulting in a low carbon content in the fragments in the result.

[0083] By comparing Example 1 with Comparative Example 5, it can be seen that when the proportion of the upper dispersion liquid removed is too high, it will also lead to the mixing of the fragment carbon species and the non-fragment carbon species, resulting in a low fragment carbon content in the result.

[0084] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for detecting the carbon content of fragments in a lithium iron phosphate positive electrode material, characterized in that: include: Dispersing the lithium iron phosphate positive electrode material in a solvent to obtain a dispersion liquid, and subjecting the dispersion liquid to a static treatment; wherein, based on the mass of the lithium iron phosphate positive electrode material being 1 g, the amount of the solvent used is not less than 30 mL; the dispersion time is 10-60 min, and the static treatment time is not less than 40 min; the density of the solvent is lower than that of the lithium iron phosphate material; 30-60% of the total volume of the dispersion is removed from the upper layer and dried. The mass of the dried material is M1 and the carbon content is C1. The remaining dispersion is dried, and the mass of the material after drying is M2, and the carbon content is C2; The carbon content of the fragments in the lithium iron phosphate positive electrode material is calculated using the formula: (C1-C2)×M1 / (M1+M2).

2. The detection method according to claim 1, characterized in that: Based on the mass of lithium iron phosphate positive electrode material being 1 g, the amount of the solvent used is 30-100 mL.

3. The detection method according to claim 1 or 2, characterized in that: The solvent is at least one of water, ethanol, methanol, benzene and N-methylpyrrolidone.

4. The detection method according to any one of claims 1 to 3, characterized in that: The dispersion method is ultrasonic treatment.

5. The detection method according to any one of claims 1 to 4, characterized in that: The standing treatment time is 40min-10h.

6. The detection method according to any one of claims 1 to 5, characterized in that: The method of removing the dispersion liquid includes at least one of quantitative aspiration and centrifugation.

7. The detection method according to claim 6, characterized in that: The method of removing the dispersion is quantitative aspiration.

8. The detection method according to any one of claims 1 to 7, characterized in that: The drying process is carried out by oven drying.

9. The detection method according to any one of claims 1 to 8, characterized in that: The carbon content is detected by an instrument.

10. The detection method according to claim 9, characterized in that: The instrument is a high-frequency infrared carbon-sulfur analyzer.

Citation Information

Cited By

  • Evaluation method of lithium iron phosphate surface carbon coating integrity and carbonization degree

    CN122217903A